2015
DOI: 10.1371/journal.pgen.1004873
|View full text |Cite|
|
Sign up to set email alerts
|

Systemic Delivery of MicroRNA-101 Potently Inhibits Hepatocellular Carcinoma In Vivo by Repressing Multiple Targets

Abstract: Targeted therapy based on adjustment of microRNA (miRNA)s activity takes great promise due to the ability of these small RNAs to modulate cellular behavior. However, the efficacy of miR-101 replacement therapy to hepatocellular carcinoma (HCC) remains unclear. In the current study, we first observed that plasma levels of miR-101 were significantly lower in distant metastatic HCC patients than in HCCs without distant metastasis, and down-regulation of plasma miR-101 predicted a worse disease-free survival (DFS,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 46 publications
3
67
0
Order By: Relevance
“…Under-expression of miR-101 has been identified herein as well as in previous studies in liver cancer [66,67] and CCA [68]. Down- regulated miR-101 was associated with hepatitis B virus infection [69].…”
Section: Figuresupporting
confidence: 75%
“…Under-expression of miR-101 has been identified herein as well as in previous studies in liver cancer [66,67] and CCA [68]. Down- regulated miR-101 was associated with hepatitis B virus infection [69].…”
Section: Figuresupporting
confidence: 75%
“…The binding site for miR-101 at 3′-UTR of SUB1 is indicated (Figure 1a). MiR-101 is known to play tumor suppressor function by targeting several oncogenes including EZH2, 11 proteasome assembly factor POMP, 13 Cyclooxygenase-2 (COX2), 12 and others, we sought to determine its role in SUB1 regulation. We treated prostate cancer cell line DU145 with precursor miRNA, miR-101 and tested some of the potential targets.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that serum miR-101 can serve as a potential non-invasive biomarker to differentiate HBV-HCC from HBV-LC. Recently, it was shown that enforced overexpression of miR-101 by lentivirus-mediated systemic delivery strongly inhibits HCC in vivo by repressing multiple molecular targets such as EZH2, STMN1, COX2 and ROCK2 and blocking angiogenesis and epithelial-mesenchymal transition of HCC cells (Zheng et al, 2015a).…”
Section: Mir-101mentioning
confidence: 99%